THE CARTOON, THE NEW WEAPON OF THE FIRST WORLD WAR (Journal of the Spanish Institute for Strategic Studies, 2018)
Radio, cinema, television, the internet… The mass media have evolvedover the course of time, yet what remains unchanged has been governments’or lobbies’ interest in keeping them under their control, witha view to influencing society’s thinking and ideology. In war and anyother periods of conflict, this control over information has been a matterof national concern. In fact, during the Great War, despite limitedmedia outreach capability when compared with the immediacy, capacityand penetration of today, governments realised the huge benefit thatthey could obtain from their use for propaganda purposes to supportthe war effort. One of the simplest means was the graphic publication,which may encompass comics, daily or regular strips, cartoons and posters.The objectives of this article are twofold: firstly, to analyse the realimpact of graphic publications on society during World War I; andlastly, to provide a different viewpoint for the study of any war throughits visual propaganda.